Reducing gender differences in student motivational‐affective factors: A meta‐analysis of school‐based interventions. (17th May 2022) - Lesperance, Kaley; Hofer, Sarah; Retelsdorf, Jan; Holzberger, Doris
Abstract: Background: Research shows that gender differences tend to exist in student motivational‐affective factors in core subjects such as math, science or reading, where one gender is stereotypically disadvantaged. Aims: This study aimed to investigate strategies that could reduce these gender differences by conducting a meta‐analysis on school‐based intervention studies that targeted student motivational‐affective factors. We therefore evaluated whether interventions had differential effects for male and female students' motivational‐affective factors in a given academic subject. We also evaluated potential moderator variables. Method: After conducting a systematic database search and screening abstracts for inclusion, we synthesized 71 effect sizes from 20 primary studies. All included studies were conducted in science or mathematics‐related subjects, which are stereotypically female‐disadvantaged. Results: While the interventions had significant positive effects for both genders, there was no statistically significant difference between the two genders with regard to the intervention effects on motivational‐affective factors. However, the descriptive effect size for female students ( g  = .49) was far greater than for male students ( g  = .28). Moderator analyses showed no significant effects for grade level, intervention duration, or school subject, but there was a significant influence of intervention method used. Conclusions: This study demonstrated that school‐based interventions have positive effects on motivational‐affective factors for both genders. It also provides evidence that interventions in subjects where female students are stereotypically disadvantaged may have greater effects for females than for males. Implications and suggestions for future research are discussed.